Artificial miRNAs Targeting Mutant Huntingtin Show Preferential Silencing In Vitro and In Vivo - Alex Mas Monteys; Matthew J Wilson; Ryan L Boudreau; Ryan M Spengler; Beverly L Davidson (Elsevier, 2015)
Huntington's disease (HD) is a dominantly inherited neurodegenerative disease caused by CAG repeat expansion in exon 1 of huntingtin (HTT). Studies in mouse models of HD with a regulated mutant transgene show that continuous mutant allele expression is required for behavioral and pathological signs; when mutant HTT expression declined, neuronal degeneration improved. To date, it is unknown whether neural cells in the adult human brain can tolerate reduction in both normal and mutant alleles. Thus, it may be important to develop allele-specific silencing approaches. Several siRNA sequences targeting the CAG expanded motif or prevalent single-nucleotide polymorphisms (SNPs) in linkage disequilibrium with the mutant allele have been designed and their selectivity demonstrated in vitro. However, it is unknown whether these allele-specific siRNAs will retain their specificity when expressed from artificial RNAi platforms. Here, we designed CAG- and SNP- targeting artificial miRNAs and demonstrate that some, but not all, retained their selectivity in vitro using an allele-specific reporter system and in vivo in a transgenic mouse model developed to express normal and mutant human HTT alleles.